E-068 Dual Lumen Balloon Assisted Pre-operative Embolization With Onyx for Hypervascular Head and Neck Tumors. (26th July 2014) - Mortazavi, S; Tummala, R; Grande, A; Moen, S; Jagadeesan, B
Abstract : Introduction: Pre-operative embolization of hypervascular head and neck tumors can be achieved using particulate agents or liquid embolic agents. Particulate agents are preferable due to the lower cost. However, the presence of intra-tumoral arteriovenous shunts in these tumors may occasionally result in shunting of particles to the pulmonary circulation with the risk of pulmonary or paradoxical embolism. Liquid embolic agents too may be shunted to the venous side. Additionally, there may be reflux of liquid embolics into the proximal external carotid artery or the common carotid. Therefore, reducing the flow rate into the tumor during trans arterial injection of a liquid embolic agent as well as preventing unwanted reflux of the liquid embolic agent may be advantageous. Herein, we report our experience in the embolization of hypervascular head and neck tumors with high flow intra-tumoral arteriovenous shunts using a dual lumen balloon microcatheter and Ethylene Vinyl alcohol Co-polymer (Onyx). Material and Methods: A series of four patients, 4 patients with glomus jugulare and one with Juvenile Nasopharyngeal Angiofibroma (mean age 34 years, 2 males and 2 females) underwent pre-operative tumor embolization. In all patients, transarterial embolization was initially attempted using particle agents. However, the presence of high flow intra-tumoral arteriovenous shunts prevented achievement of tumor ischemia even when large particles (300–500 microns) were used. Thereafter, embolization was performed by navigating a dual lumen Sceptre C balloon microcatheter into one or more of the arterial feeders to the tumor, inflating the balloon and then injecting Onyx 18 into the tumors through the balloon-microcatheter. Results: We were successfully able to navigate a 4 × 10 mm Sceptre C balloon microcatheter into one or more arterial feeders arising from the external carotid artery branches (ascending pharyngeal or occipital or internal maxillary arteries) such that the tip of the microcatheter was close to the tumor in each instance. We were then able to achieve excellent penetration of Onyx into the tumor beds in every instance following injection of Onyx 18 after balloon inflation. There was no instance of embolization of Onyx into the draining venous system or the lungs. There was also no instance of reflux of Onyx into the parent artery. There were no immediate clinical complications. Mean fluoroscopy time was 51.2 min (AP and lateral), and all patients subsequently underwent successful tumor resection. Conclusion: Balloon assisted Onyx embolization performed by transarterial injection of Onyx through a dual lumen balloon microcatheter may be a safe and efficient alternative to other methods for pre-operative embolization in the case of highly vascular skull base tumors with high flow intra-tumoral arteriovenous shunts. Disclosures: S. Mortazavi: None. R. Tummala: None. A. Grande: 2; C; Covidien. S. Moen: None. B. Jagadeesan: 2; C; Microvention, Covidien, Lake Regional.